2016
DOI: 10.5249/jivr.v9i1.852
|View full text |Cite
|
Sign up to set email alerts
|

Injury epidemiology in Iran: a systematic review

Abstract: Abstract:Background:Injuries are the second greatest cause of mortality in Iran. Information about the epidemiological pattern of injuries is effective in decision-making. In this regard, the aim of the current study is to elaborate on the epidemiology of injuries in Iran through a systematic review. Methods:Required data were collected searching the following key words and their Persian equivalents; trauma, injury, accident, epidemiology, prevalence, pattern, etiology, risk factors and Iran. The following dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…For example, a review study in Iran demonstrated that the mean age of people involved in traffic accidents was 30 years, and more than three-quarters of the patients were men. 19 Similar to their counterparts in most low-income countries (e.g., Afghanistan 20 ) and middle-income countries compared to high-income countries, Iranian men seem to be more vulnerable to injuries because of Iran’s specific socio-cultural conditions (more driving, more occupational threats, injuries from violence, and the like). 19 , 21 However, as people’s age increases, they are more likely to undergo more severe outcomes, such as hospitalization and death.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, a review study in Iran demonstrated that the mean age of people involved in traffic accidents was 30 years, and more than three-quarters of the patients were men. 19 Similar to their counterparts in most low-income countries (e.g., Afghanistan 20 ) and middle-income countries compared to high-income countries, Iranian men seem to be more vulnerable to injuries because of Iran’s specific socio-cultural conditions (more driving, more occupational threats, injuries from violence, and the like). 19 , 21 However, as people’s age increases, they are more likely to undergo more severe outcomes, such as hospitalization and death.…”
Section: Discussionmentioning
confidence: 98%
“… 19 Similar to their counterparts in most low-income countries (e.g., Afghanistan 20 ) and middle-income countries compared to high-income countries, Iranian men seem to be more vulnerable to injuries because of Iran’s specific socio-cultural conditions (more driving, more occupational threats, injuries from violence, and the like). 19 , 21 However, as people’s age increases, they are more likely to undergo more severe outcomes, such as hospitalization and death. The findings of a study in Taiwan revealed that, compared to other adults injured in traffic accidents, elderly trauma patients had higher injury severity, less favorable outcomes, and a higher rate of admission to the ICU.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is essential to identify and target high-risk populations, such as individuals who engage in risky behaviors [ 5 ]. Even though Iran has a mandatory seatbelt and helmet legislation and alcohol consumption is prohibited by law, risky behaviors including drunk-driving, speeding, and refusing to wear helmets, seatbelts, and car seats for children continue to be risk factors for different injuries among Iranian people [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the Mean±SD injury severity score was equal to 8.1±8.6; however, this study did not specifically examine vascular injuries. Only a few related studies were reviewed in this field [31]; thus, estimating the prevalence of trauma is essential for this group of patients [32,33].…”
Section: Introductionmentioning
confidence: 99%